145 Relationship between working condition and health-related quality of life among Korean school cooks for lunch services. (11th October 2013) - Choi, M; Lee,; Lee,; Kim,
Abstract : Objectives: This paper investigates the health-related quality of life (HQOL) among Korean school cooks for lunch services, especially focusing on the relationship between working conditions and their physical and mental HQOL. Methods: A cross-sectional study of 1, 397 school cooks in one province was carried out, using a mail survey from June to October 2012. Working conditions and HQOL were determined through structured self reported questionnaires. To evaluate working conditions, subjective labour intensity was investigated using Borg scale, and the numbers of both daily working hours and meals assigned per cook were questioned. HQOL was determined by applying 'Korean SF-8.' To evaluate the degree of association between working conditions and HQOL, odds ratios were estimated after adjusting for demographic factors, such as age, education, chronic disease, exercise and drinking habits by logistic regression. Results: All of respondents were female, and the mean age was 47.8 (S. D = 5.36). School cooks assigned more than 120 meals showed statistically significantly lower HQOL scores both in physical (OR = 1.48, 95% CI = 1.03–2.13) and mental (OR = 1.47, 95% CI = 1.03–2.10) criteria than those who were assigned less than 90. Workers who responded that 'My work is hard' (13≤Borg scale≤16) or 'My work is very hard' (17≤Borg scale≤20) have significantly lower physical (OR = 3.47, 95% CI = 2.47–4.86) and mental (OR = 1.88, 95% CI = 1.36–2.59) HQOL scores than those who did not (6≤Borg scale ≤12). The number of daily working hours was not significantly related to physical and mental HQOL scores. Conclusions: The degree of subjective labour intensity and the number of meals assigned per cook were related to the physical and mental HQOL of school cooks for lunch services. Since cooks assigned more than 120 meals have significantly lower physical and mental HQOL scores, the number of lunch meals assigned per cook should be reduced.